Fatores associados ao risco de morte por suicídio após hospitalização psiquiátrica no Brasil (2002-2015) - Camila Mendes Guimaraes (2021)
Introduction - Patients with psychiatric disorders are considered to be at increased risk for suicide compared to the general population and the risk is substantially higher after discharge from psychiatric hospitalization. Efforts have been made to identify factors related to the increased risk of suicide in this population. Objective - This study aimed to investigate sociodemographic and clinical characteristics in general and stratified by sex associated with the risk of death by suicide within 365 days after hospital discharge in patients admitted to psychiatric hospitalization in the Unified Health System (SUS). Methods - Non-concurrent prospective cohort study using secondary data from adult patients admitted to psychiatric hospitalization in the SUS from 2002 to 2014. The patients were characterized by sociodemographic and clinical variables. Adjusted hazard ratios (AHRs) of suicide within 365 days after hospital discharge were estimated by Cox proportional hazards regression models in general and stratified by sex. Results - We selected a total of 1,228,784 patients admitted to psychiatric hospitalization in the SUS of which 3,201 died by suicide within 365 days after hospital discharge. We found increased risk of suicide for the following variables: male gender (AHR, 1.88; 95% CI, 1.73-2.05), adults aged 18 to 29 years (AHR, 1.55; 95% CI, 1.32-1.82), living in South region of Brazil (AHR, 1.46; 95% CI, 1.35-1.57), living in rural (AHR, 1.57; 95% CI, 1.42-1.72) or intermediate municipalities (AHR, 1.39; 95% CI, 1.21-1.59). In relation to psychiatric diagnosis, patients with depressive disorders (AHR, 3.87; 95% CI, 3.41-4.38) had the highest risk for suicide after hospital discharge with stronger association among men compared with women. The second highest risk was obtained for opioid use disorders (AHR, 2.71; 95% CI, 2.00-3.67), with a particularly strong association among women compared with men. In the general model, personality disorders (AHR, 2.59; 95% CI, 1.85-3.64) and bipolar disorders (AHR, 1.89; 95% CI, 1.64-2.19) were associated with an increased risk of suicide after hospital discharge. Compared with patients who had only one psychiatric hospitalization, patients with 2 (AHR, 1.59; 95% CI, 1.45-1.75) or 3 or more (AHR, 2.05; 95% CI, 1.89-2.22) psychiatric hospitalizations had an increased risk of dying by suicide within 365 days after hospital discharge. Conclusions - Patients previously admitted to psychiatric hospitalization should have access to mental health services immediately and for a long-term after discharge. The treatment of mental disorder is a priority measure in preventing suicide. Differences in the risks of suicide after psychiatric hospital discharge highlight the need for specific prevention programs by sex, age group, place of residence and psychiatric diagnosis. Furthermore, these results influence clinical decisions related to discharge and post-discharge follow-up.